PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VII SMP NEGERI 15 PADANG - Rahmi, Yulfita (Departemen Matematika, 2023)
Students must learn to communicate mathematical concepts. Mathematical communication abilities in class VII SMPN 15 Padang are still lacking, according to observations and assessments. Applying Think Talk Write (TTW) cooperative learning model to solve this challenge. The final goal of this research is to determine whether students who use the TTW type cooperative learning model in class VII SMPN 15 Padang have better mathematical communication skills than those who use conventional learning and to determine their ability development. Descriptive and quasi-experimental methods are used in this study. This test featured a quiz and final math communication test. The mathematical communication ability test analysis yielded P-value = 0.028 and α = 0.05. The TTW type cooperative model affects students' mathematics communication since the P-value < α..Keywords– Mathematical Communication Skills, TTW, Conventional Learning